Construction of graphene oxide based mixed matrix membranes with CO2-philic sieving gas-transport channels through strong π–π interactions. Issue 37 (5th September 2018) - Cong, Shenzhen; Li, Hui; Shen, Xiangjian; Wang, Jing; Zhu, Junyong; Liu, Jindun; Zhang, Yatao; Van der Bruggen, Bart
Abstract : Two-dimensional nanomaterials can be used to create innovative membranes with high permeability and selectivity, but precise manipulation of laminar stacking and the construction of ordered, CO2 -philic molecular sieving channels remains a technological challenge. Abstract : Two-dimensional nanomaterials can be used to create innovative membranes with high permeability and selectivity, but precise manipulation of laminar stacking and the construction of ordered, CO2 -philic molecular sieving channels remains a technological challenge. Here, gas separation membranes containing advanced CO2 -philic nano-laminar clusters in the interlayer channels of graphene oxide (GO) were formed by the intercalation of an o -hydroxya porous organic polymers (POPs) into GO. POPs are phenolic azo-hierarchically mesoporous polymers; the azo group of POPs allows to reject N2, while the unreacted phenolic groups on the POP surface have a high CO2 -philic and nanocephalic character. Beyond that, the introduced POPs could tailor the interlayer height of graphene oxide-assembled 2D nanochannels and feature an ordered structure of such graphene oxide nanosheets. Therefore, POP–GO may facilitate a superior CO2 /N2 separation performance for the membrane because of the synergetic effect of GO and POPs. The POP–GO membrane was found to have a high CO2 permeability of 696 barrer and a CO2 /N2 ideal selectivity of 51.2, which is beyond Robeson's upper bound (2008). The d -spacing of graphene oxide after adjustment is approximately 3.5 Å according to a Density Functional Theory (DFT) simulation; this is between the dynamic radius of CO2 and N2 . This approach potentially offers the opportunity to precisely manipulate the d -spacing of graphene oxide through chemical bonds, which has potential for large-scale applications compared to conventional vacuum-assisted filtration.